PENDAMPINGAN & PELATIHAN BERWIRAUSAHA IBU-IBU PETANI JAGUNG - Usman Usman; Veneranda Rini Hapsari (Jurnal Pengabdian Masyarakat Khatulistiwa, 2020)
Abstract The problem faced by corn farmers is that the quality of corn prices is not in accordance with the market price because they do not drain well so that prices in the market have fallen considerably. The role of corn is very important and beneficial for human and animal life. And it is the second staple food after rice. While in the world corn ranks third after wheat and rice. The advantage of corn itself is that the harvest time is faster and very resistant to pests and diseases and higher production. (Ermanita, 2004). Indonesia is a tropical climate and fertile soil and as a country known as an agrarian nation, Indonesia is a country known for its rich biodiversity which is a mainstay in the fields of food, industry and energy. As an industrial material corn can be processed into processed oils, corn flour, sugar and others. The method used in this service is a method of training and teaching that is discussion, teaching method, participants of the training are housewives in the Farmer Business group. They are given material about how to make cakes so that they can be of selling value., Using the method (Discussion Method) Trainees are given the opportunity to discuss issues related to corn, using the interview method. The trainees were given the opportunity to be interviewed how much influence the training on baking for them in developing themselves.Keywords: ASSISTANCE, ENTREPRENEURSHIP,TRAINING FOR CORN  FARMERS